The Correlation between Lifestyle and Stress with Pre-menstruation Syndrome in Nursing Students at Universitas Muhammadiyah Purwokerto - Anisa Wening Filisiana; Supriyadi Supriyadi (UM Purwokerto Press, 2024)
Background: Premenstrual syndrome (PMS) is a collection of physical and psychological symtomps experienced by reproductive-aged women between 3-7 days before menstruation and disappear when menstruation begins. If not addressed, it can impact the productivity and health of women. Lifestyle and stress are believed to be the causes of PMS. Method: This quantitative study used a descriptive-analytic design with a cross-sectional approach. The sampling technique used random sampling with a total of 39 respondents. Results: The results of the chi-square test showed that physical activity had a p-value of 0.000 (p<.05), sleep patterns had a p-value of 0.000 (p<0.05), diet had a p-value of 0.000 (p<0.05), and stress had a p-value of 0.000 (p<0.05). The research results indicate that there is a significant correlation between lifestyle and stress with the occurrence of premenstrual syndrome in nursing students at Universitas Muhammadiyah Purwokerto. Conclusion: There is a correlation between lifestyle and stress with the occurrence of premenstrual syndrome in female nursing students at Universitas Muhammadiyah Purwokerto.